Research on location privacy in mobile internet - Yu-hang WANG; Hong-li ZHANG; Xiang-zhan YU (Tongxin xuebao)
The related researches on location privacy in mobile internet were surveyed comprehensively,dissertate sepa-rately from the perspective of LBS(location-based services) and location service.First the privacy protection approaches for LBS were detailed,their features in the view of privacy attacks and LBS applicability were researched.Then the es-sence and research boundary of location privacy in location service were demonstrated,its related research progress and policies were introduced.The future research directions are provided in the end.